(3cJGH ChWhdhbS aj GdWdhYGJ hGdZQhHGJs - (3GhWhdhbSs
(3ChdgG (B:s
(3Cf HYV WdhYGJ GdchGcH GdJi djSJ eJMjQI hZQhHGJgG jbGd dgG NajI hHYVgG XGgQI s
(3BNQgG (B:s
(3aPdc GdHQhL hgh GdReGf GdPi eQJ ajg GdTeS JeJ GdebGdI GdKGfjI ef cJGH ChWhdhbS ai GdWhdYGJ GdZQhHGJ hGfbVi GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1435s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3Gdadcs